Social Media Analytics: Analyzing User Engagement and Marketing Strategies across Popular Platforms - ELANGO, DINESH; Sithambalam, Yamuna (Journal of Research and Multidisciplinary, 2025)
In the contemporary digital landscape, social media platforms have advanced into essential tools shaping the way individuals intermingle, exchange information, and engage with assorted content. Concurrently, businesses and marketers recognize the immense potential of these platforms as invaluable channels to reach, connect, and resonate with their target audiences. This comparative study delves into the realm of social media analytics, employing an analysis of secondary data sourced from prominent platforms like Twitter, Facebook, and Instagram. The primary objective of this research is to discern variations in user engagement and evaluate the effectiveness of marketing strategies across these diverse platforms. By harnessing insights from secondary data, this study endeavors to illuminate the distinctive strengths and weaknesses of each platform concerning user interactions, content performance, and marketing success. The findings of this research endeavor to equip businesses and marketers with valuable knowledge for fine-tuning their digital marketing strategies, tailoring them to optimize engagement levels and enhance overall brand visibility in the ever-evolving landscape of social media dynamics.